Effects of nonuniform incident velocity on a dynamic wind turbine airfoil. (20th January 2014) - Gharali, Kobra; Johnson, David A.
Abstract For further insight into the performance of a horizontal axis wind turbine blade section under yaw loads, a 2D numerical simulation of a pitching S809 airfoil under dynamic stall with an unsteady incident velocity is presented. The streamwise incident velocity and pitch angle of incidence oscillated with the same frequency but with a range of phase differences, − π ≤ Φ ≤ π. Changing Φ caused variation of the results, which can be highlighted as significantly augmented and dramatically damped dynamic stall loads, both increasing and decreasing trends for vortex growth time during Φ increase, a shifted location of the maximum loads and a change in the order of the vortex pair circulation in each cycle. The results showed strong dependency on the velocity and acceleration of the freestream during dynamic stall, which categorized the results in four individual subdomains with different behaviors. Copyright © 2014 John Wiley & Sons, Ltd.